Diseño de una máquina neumática semiautomática para aplicar gota de resina de poliuretano flexible (Doming) en superficies planas no porosas - Zambrano Peralta, Javier Alberto (2015)
In the present work has been designed a pneumatic machine semi-automatic to implement drop of flexible polyurethane resin (doming) in flat non-porous surfaces with the aim of improving the way of production of the encapsulated in resin (doming), this process is done by the graphic designers of manually, do not use automated machinery or semi-automated, because there are no within the country and its import is expensive. Its design is justified because the doming products that come from abroad are of very low costs and you can't compete that there is no machine to make the process more quickly and avoid loss of time and in this way lower costs. Using an appropriate methodology were selected several alternatives for the design and simulation of the main systems, using the program Solids Works, considering different criteria of essential importance. Conducting a comparative study and weighting of criteria of machinery, it is proceeded to select a series of alternatives, the one that best meets the requirements posed to the design of the machine. Subsequently be dimensioned all systems that are the semi-automatic pneumatic machine to apply resin, taking into account all the requirements involved, such as: the market, service life, material strength, among others, so that there is an optimal design of each element of the machine. Are the levels of workshop of the pneumatic machine to apply resin semi-automatic, which illustrates how to construct the elements previously designed, establishing the dimensional and geometrical tolerances required as well as the machine tools to be used for the processing of the raw material.